Teresina Entrepreneurs: profile and history of life (Research, Society and Development, 2022)
This research studies female entrepreneurship. The objective is to present and discuss the characteristics of women entrepreneurs in Teresina-PI. An exploratory qualitative research is carried out with a sample of 20 women entrepreneurs that are included in the SEBRAE-PI database; for data collection, interviews with closed questions for demographic data, values, a script on life history and motives are used. Content analysis and descriptive statistics are used. As a result, the sample has a high age range, are married, from a large and low-income family, and undertook by necessity. Its main instrumental values are: honest, courageous; main terminal values: family security, true friendship. The reason identified is affiliantion. It is concluded that the research will contribute to support and promotion entities, considering the profile found, reinforce their action programs. Discussions with entrepreneurs about their own profile will serve for self-improvement.